Peran manajemen strategi dalam pengelolaan modal koperasi simpan pinjam untuk pertumbuhan ekonomi berkelanjutan - Ramadhani, Miagasela Aprilia (Maliki Interdisciplinary Journal, 2025)
Amidst the tight national competition and challenges of globalization, savings and loan cooperatives have great potential in improving the local economy and. However, many cooperatives have not implemented effective management strategies, resulting in suboptimal resources. Through literature analysis, this study identifies various challenges faced by cooperatives, including a lack of understanding of management strategies and limited resources. This study also highlights the importance of implementing SWOT analysis to formulate appropriate strategies, as well as product development, digital services, and financial education as innovative steps in improving cooperative performance. With a systematic approach, it is hoped that savings and loan cooperatives can maximize the use of capital and increase profitability. These findings provide insight into how effective management strategies can contribute to the sustainability and economic growth of cooperatives. The research method used in this study is a literature review, in which the author reviews various previous studies to collect relevant information and data regarding the management of savings and loan cooperative capital and the implementation of management strategies. Through this method, the author can gain a more comprehensive understanding of the issues faced by cooperatives and possible solutions to improve their performance.